PENGARUH PELATIHAN DAN PENGEMBANGAN SUMBER DAYA INSANI TERHADAP KINERJA ISLAMI KARYAWAN PADA PT JAMKRINDO CABANG SURABAYA - Hardityo, Alam Fabian; Fahrullah, Arasy (Universitas Negeri Surabaya, 2021)
The purpose of this research is to analyze theinfluenceof training and human resource development withIslamic employee performance ofPT Jamkrindo on Surabayabranch. The author use a quantitive research method with an assosiative approach.Thenumber of samples in this research are25 respondents. Data collection techniques in this study used a questionnaire and measured with a Likert scale and then processed and with IBM SPSS Statistics 25software. The results of this study indicate that trainingand development, each of which has a significant effect on Islamic employee performance. The training and development variable has a correlation of 81,6%, which means that training and development variable has a positive contribution of Islamic employee performance and the remaining 18,4% is obtained from other elementnot examined in this study